A REVIEW OF GEOPHYSICS STUDY OF GRAPHITE OCCURRENCES IN BALAI SEBUT COMPLEX, SANGGAU, WEST KALIMANTAN - Maulana, Rizki Fajar; Sulyana, Deska; Meirawaty, Mira; Yuda, Himmes Fitra; Hendrasto, Fajar; Wijaya, Budi; Apriniyadi, Mohammad (Universitas Trisakti, 2025)
Graphite is a non-metallic polymorph mineral formed by carbon. Graphite has become indispensable in the worldwide industry due to its widespread applications, such as industrial uses, energy transition, and even electricity. It is a critical anode element for lithium-ion batteries. Graphite has unique physical characteristics. It has a very low specific gravity and is an extraordinarily soft but highly conductive material. It is exceptionally heat-resistant, making it applicable in metallurgy and manufacturing. Due to all characteristics, graphite occurrences in Indonesia are slightly unknown. In contrast, there is a possibility, according to some Palaeozoic metamorphic host graphite in several parts of Indonesia. This study will enlighten early-step exploration of graphite potency in Balai Sebut, Sanggau Regency, and West Kalimantan. We combined airborne and ground geophysics using Active Directory Magnetotelluric (ADMT) tools to estimate graphite distribution on the surface and subsurface. We also did laboratory analysis to validate graphite content using petrography analysis, X-ray diffraction (XRD), and carbon analyzer (LECO) of some representative graphite-bearing rock from fieldwork. Graphite in the research area is exposed to the surface, like in Empiyang, whereas potential graphite in the Terati area lies 0-6 m below the subsurface. Petrographic analysis shows that graphite occurs as flake graphite that is characterized by widespread distribution with low thickness. Both LECO and XRD confirmed the occurrence of these graphite-bearing rocks, with the total amount of graphite ranging from 0.91‒1.58%. This research is expected to provide suggestions in the early stage of graphite exploration based on thematic cases as graphite occurrences in the Balai Sebut area.